The chosen we : Black women's empowerment in higher education - Winkle-Wagner, Rachelle (State University of New York Press, 2023)
Draws on and centers oral histories with Black women college graduates to demonstrate the role of community in fostering their success in and beyond education.
Keywords: African American women -- Education (Higher); African American women college students -- Social conditions.; African American college graduates -- Interviews.; African American women -- Interviews.; Universities and colleges -- United States -- Sociological aspects.; Education, Higher.; Electronic books.; Étudiantes noires américaines -- Conditions sociales.; Diplômés d'université noirs américains -- Entretiens.; Noires américaines -- Entretiens.; Universités -- États-Unis -- Aspect sociologique.; Enseignement supérieur.; Livres numériques.; higher education.; e-books.; EDUCATION / Higher.; African American college graduates; African American women; Universities and colleges -- Sociological aspects; United States; Interviews